Evaluation of micronutrient and nutritional status among preschool children in Jordan: results from a Nationwide survey - Barham, Rawhieh; Tayyem, Reema; Al-Majali, Lama; Al-Khatib, Buthayna; Al Jawaldeh, Ayoub (Frontiers in Nutrition, 2024)
Background: Jordan has shifted from issues of undernutrition to rising rates of overweight and obesity, while still dealing with micronutrient deficiencies. The 2010 national survey revealed high rates of iron and vitamin D deficiencies among preschool children, with about 20% experiencing vitamin A deficiencies. The goals of the 2019 Jordan National Micronutrient & Nutrition Survey (JNMNS) include assessing feeding practices of infants and young children, determining the frequency of consuming micronutrient-rich foods, evaluating causes of anemia, assessing the health status of specific subgroups, and comparing findings to the 2010 survey. Methods: JNMNS 2019 was a comprehensive national cross-sectional survey structured across four strata. Within each stratum, 40 primary sampling units were chosen in proportion to their size based on the 2015 Jordan census. Subsequently, the Department of Statistics conducted household listings in each PSU. Separate response rates were assumed for households and target groups, encompassing interviews, anthropometric measurements, and specimen collection. The survey aimed to collect data from 2,210 households, including interviews and anthropometry for 1,232 preschool children, with blood samples obtained from 992 of them. Results: The findings revealed no severe anemia cases, but 11% of preschoolers aged 12-59 months were anemic. Iron deficiency affected 22.4%, with 5% having iron deficiency anemia. Vitamin D deficiency increased to 22.9% in 2019. Stunting and wasting rates improved slightly to 6.3% and 0.1%, respectively. Overweight and obesity rates remained stable at 6.2% and 2.1%. Anemia decreased by 5-6%, but iron deficiency rose by 7%. Vitamin A deficiency decreased, but iron deficiency anemia remained largely unchanged. Undernutrition was rare, but vitamin D deficiency affected 27.7% of preschoolers, impacting growth and immunity. Iron deficiency, affecting 25% of children, poses a risk to cognitive development. Overweight or obesity affected 9% of children, a medium public health issue according to the WHO. Conclusion: Although severe anemia was rare, 11% were anemic, and 22.4% had iron deficiency, including 5% with iron deficiency anemia. Vitamin D deficiency affected 22.9%, impacting growth and immunity. While stunting and wasting improved, childhood overweight and obesity rates remained steady. Anemia decreased, but iron deficiency rose by 7%.